The Desperation Of Father In Great Depression Era As Seen In Arthur Miller’s The Death Of Salesman - Sri Megawati (Jurnal Ilmiah Langue and Parole, 2017)
The title of this thesis is an analysis of the ambitions and dreams of Americans in the 1920s, focusing on the analysis of a leading figure from the circle An ordinary person named Willy Loman who turned his career into a businessman (Salesman), but eventually found failure and experienced severe frustration and eventually committed suicide by crashing the car fence home. Problems in this thesis is a problem associated with characterizations such as Willy Loman has an inner conflict between his two children Biff and Happy. In this thesis, the author uses a psychological approach. This approach saw the development of characters in literary works that are a reflection of the true human psyche. This approach also explains the character changes in the main characters. The purpose of this study is for the reader to know the ambitions and dreams of what is in the drama of the death of Salesman, and the results obtained from this analysis is that material satisfaction greatly affects the lives of Americans especially Willy loman, the main character in this drama he Very ambitious to achieve material satisfaction such as home, money, success, wealth, honor, equality of rights so that people around him will put respect and sympathy.